Determination of metabolizable energy value of corn with different average geometric diameters for european quails (Coturnix coturnix coturnix) - Marcelo José de Mello Rezende (Brazilian Archives of Biology and Technology, 2009)
Metabolizable energy (ME) of corn with different geometric diameters was determined in European quail with 26 days of age with 124 g of mean live weight, using the Total Collection of Excreta Method. One hundred and twenty five quails were divided in five treatments, five replications with five quails each, with one treatment used to determine endogenous losses. Values of Average Geometric Diameter (AGD) of the corn were 600, 800, 1000 and 1200 µm. ME of corn was not affected by AGD. Average values were 3079, 3274, 3300, 3137 Kcal/kg respectively for apparent metabolizable energy, corrected apparent metabolizable energy, true metabolizable energy, corrected true metabolizable energy. Determinou-se o valor de energia metabolizável (EM) do milho com diferentes diâmetros geométrico médio em codornas com 26 dias de idade e 124 g de peso médio, utilizando-se a metodologia da coleta total de excretas. Foram utilizadas 125 codornas distribuídas em cinco tratamentos com cinco repetições de cinco aves, sendo um tratamento para determinar as perdas endógenas. Os valores de diâmetro geométrico médio (DGM) do milho estudado foram 600, 800, 1000 e 1200 µm. O DGM não apresentou influência significativa sobre a EM do milho que apresentou valores médios de 3079, 3274, 3300, verdadeira, energia metabolizável verdadeira corrigida.